2022
DOI: 10.1515/ev-2022-0022
|View full text |Cite
|
Sign up to set email alerts
|

EU Green Taxonomy Data – A First Vendor Survey

Abstract: This paper aims to explain key concepts of the EU Taxonomy for Sustainable Activities, a common classification system established to clarify which investments are environmentally sustainable. Additionally, it provides insight on the compliance of corporate activities with the EU Taxonomy’s criteria based on a first survey on market data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…Unfortunately, the details of the various approaches are not available, as the actual models mapping firms' information from annual reports and other inputs to the Taxonomy are proprietary. Hence, it is impossible to understand how the data providers come to their detailed assessments of Taxonomy alignment and why they sometimes disagree substantially, as shown in Hoepner and Schneider (2022).…”
Section: Bottom-up Versus Top-down Estimates Of Greennessmentioning
confidence: 99%
“…Unfortunately, the details of the various approaches are not available, as the actual models mapping firms' information from annual reports and other inputs to the Taxonomy are proprietary. Hence, it is impossible to understand how the data providers come to their detailed assessments of Taxonomy alignment and why they sometimes disagree substantially, as shown in Hoepner and Schneider (2022).…”
Section: Bottom-up Versus Top-down Estimates Of Greennessmentioning
confidence: 99%
“…The taxonomy was also addressed in a study by Hoepner and Schneider (2022). They noted that the main purpose of the current taxonomy is to direct investment to those projects that best fit the definition of "sustainability".…”
Section: Introductionmentioning
confidence: 99%
“…The researchers argue, however, that such results are not a negative indicator in general, as they only show that the economy (and especially companies) are not yet fully prepared to move towards operating according to sustainability principles. In the future, the situation should change for the better if government authorities continue this policy [75].…”
Section: Introductionmentioning
confidence: 99%
“…This implies that the economic activity related to a specific code of the statistical classification of economic activities-Nomenclature of Economic Activities (NACE)-needs to be on the list of activities included within the DAs [8]. It is important to note that the EU taxonomy is a dynamic tool [26], subject to ongoing development, and therefore activities not currently included in the published DAs are not necessarily considered "brown" activities.…”
mentioning
confidence: 99%
“…When focusing on the corporate context (searching "corporate EU taxonomy" within the title, abstract, and keywords, limiting the search to English-language articles from 2020, when the TR entered into force, and the keyword "corporate"), a mere six relevant hits were obtained, of which three were deemed irrelevant to the research question. From the remaining publications, two new studies were identified, yet neither specifically addressed the usability of the EU taxonomy criteria; one evaluated corporate compliance with the EU taxonomy in a first vendor study [26], while the other examined its effectiveness in transitioning to sustainable corporate governance [20]. The snowballing technique was employed to explore related publications by the same authors, revealing a focus on the effectiveness of the EU taxonomy in achieving the path to climate neutrality [5,14].…”
mentioning
confidence: 99%